Smooth muscle cell-specific SOCS3 deficiency promote pericardial fibrosis and diastolic dysfunction in aging mice. (25th November 2020) - Yanai, T; Yasukawa, H; Mawatari, K; Sasaki, T; Takahashi, J; Nohara, S; Shimozono, K; Shibata, T; Okabe, K; Yamamoto, M; Fukumoto, Y
Abstract: Background: Suppressor of cytokine signaling-3 (SOCS3) is a cytokine-inducible negative regulator of signal transducer and activator of transcription-3 (STAT3) signaling pathway. We have previously shown that cardiac-specific SOCS3 deficiency spontaneously develop cardiac dysfunction with advanced age. However, the role of SOCS3 in smooth muscle cells in cardiovascular pathophysiology remains elusive. In this study, we determined whether STAT3 and SOCS3 in smooth muscle cells would play a role in cardiovascular pathophysiology. Methods and results: To target inactivation of the SOCS3 gene to smooth muscle cells, SOCS3-flox mice were bred with transgenic mice expressing Cre recombinase under control of the mouse SM22-α promoter (sm-SOCS3-KO mice). Left ventricular weight to body weight ratio was significantly increased in sm-SOCS3-KO mice compared with wild-type mice at 12 months of age (p<0.05). Echocardiographic analyses of smSOCS3-KO mice showed significantly increased left ventricular diastolic dysfunction compared with wild-type from 12 months of age (p<0.05). Sirius-red staining revealed that thickness of pericardium and cardiac interstitial fibrosis in sm-SOCS3-KO mice were markedly greater compared with wild-type mice at 12 months of age (p<0.05). Western blot analyses showed that phosphorylated STAT3 was significantly increased in sm-SOCS3-KO hearts compared with wild-type mice at 12 months of age (p<0.05), whereas no significant differences were observed at 2 months of age. To investigate the mechanism that gave rise to promoted cardiac fibrosis and diastolic dysfunction during aging in sm-SOCS3-KO, we conducted a real-time PCR array analysis for fibrosis. The expression of pro-fibrotic CTGF (connective tissue growth factor), PDGFb (platelet growth factor-b), and TGF (transforming growth factor) family genes including TGFb1, TGFb2, and TGFb3, were significantly higher in sm-SOCS3-KO hearts than those in wild-type at 6 months of age. Conclusion: Thus, smooth muscle cell-specific SOCS3 deletion induces increased pericardial fibrosis, cardiac interstitial fibrosis, and increased diastolic dysfunction in aging mice, possibly through the augmentation of pro-fibrotic growth factors. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Grant JSPS KAKENHI